The Procedure for Restructuring Budgetary Claims From Necessity to Reality - Onet, Cristina (Journal of Legal Studies, 2023)
The present work approaches the legal institution of the restructuring of budgetary claims from the perspective of the procedure to be followed by the tax debtors interested in agreeing on the need to extinguish their budgetary claims with the desire to avoid the insolvency of the company. We bring up that the restructuring of budgetary claims was thought so as to offer a helping hand, especially to large companies in a situation of major financial difficulty. This present study aims to provide a synthetic picture of the steps to be followed in order to successfully complete this procedure. For this, the procedure is divided into three stages, namely the pre-stage, the procedure itself and the completion of the procedure. The acts to be performed at the pre-stage refer to the notification of the restructuring intention, the restructuring plan and the prudent private creditor test. The stage itself of the restructuring starts with the submission of the application to the tax authority, which will be settled by it either with a decision approving the restructuring or with a decision rejecting it, or with a decision approving a payment facility. Once the restructuring is approved, it will be carried out in accordance with the restructuring plan, under the supervision of the persons designated for this purpose. During its development, the restructuring process may undergo changes that will materialize either in the modification of the restructuring plan or in the modification of the payment facilitation decision, if such a facility has been approved. Whether there is a change in the restructuring process, or not, once it has started, it will have to be completed. If the restructuring plan is successfully implemented, the fiscal debtor’s budgetary claims will be extinguished and he will be able to go on with the economic activity for which he was established. If, however, the restructuring plan fails, the tax debtor risks being subject to forced execution by the tax authority, or even to request its insolvency, which could lead to the cessation of its existence.